1988
DOI: 10.1073/pnas.85.15.5718
|View full text |Cite
|
Sign up to set email alerts
|

Paramecium calcium channels are blocked by a family of calmodulin antagonists.

Abstract: Although the voltage-sensitive Ca channel present in Paramecium has been subjected to detailed physiological and genetic analysis, no organic ligands have been described that block this channel with high affinity and that ultimately can be used to identify channel components. Based on a previous observation that the naphthalene sulfonamide calmodulin antagonist W-7 can block Paramecium Ca channels at high concentration, we have synthesized analogs of W-7 that block these channels at concentrations of <1 aiM. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…Alternatively, anti-CaM drugs can affect behavior on the basis of the effects on a variety of currents, which are activated more or less by a Ca 2 +/CaM complex. For instance, W7, i.e., N-(6-aminohexyl)-5-chloro-lnaphthalenesulfonamide, chlorpromazine, R24571 (calmidazolium), or TFP can block voltage-dependent Ca 2 + channels in cilia and, hence, block backward swimming (Haga et aI., 1982;Ehrlich et al, 1988). Inhibitory effects have been recognized with somatic Na+ currents and Kt currents, as we could confirm (Erxleben and Plattner, 1994).…”
Section: Centrin-and Spasmin-based Contractilitysupporting
confidence: 60%
“…Alternatively, anti-CaM drugs can affect behavior on the basis of the effects on a variety of currents, which are activated more or less by a Ca 2 +/CaM complex. For instance, W7, i.e., N-(6-aminohexyl)-5-chloro-lnaphthalenesulfonamide, chlorpromazine, R24571 (calmidazolium), or TFP can block voltage-dependent Ca 2 + channels in cilia and, hence, block backward swimming (Haga et aI., 1982;Ehrlich et al, 1988). Inhibitory effects have been recognized with somatic Na+ currents and Kt currents, as we could confirm (Erxleben and Plattner, 1994).…”
Section: Centrin-and Spasmin-based Contractilitysupporting
confidence: 60%
“…These compounds blocked the Ba2+ current flowing through Ca2+ channels ( Figures 3, 4 and 5) at concentrations similar to those required for the inhibition of ionic currents through Ca2+ channels in other cells (Klockner & Isenberg, 1987;Ehrlich et al, 1988). Moreover, the calmodulin inhibitors inhibited [3H]-nimodipine binding (Figure 2).…”
Section: Discussionmentioning
confidence: 98%
“…However, it has been suggested that these compounds exert effects that are not related to calmodulin inhibition when applied extracellularly (e.g., Klockner & Isenberg, 1987;Hori et al, 1989). Inhibition of Ca2`channels by these compounds was also investigated by electrophysiological techniques in cardiac cells (Klockner & Isenberg, 1987) and in Paramecium (Ehrlich et al, 1988). Klockner & Isenberg (1987) reported that several calmodulin inhibitors reduced Ca2" currents in smooth muscle cells from bovine portal vein.…”
Section: Introductionmentioning
confidence: 99%
“…W-7 has been reported to block various Ca2+ channels and currents (Greenberg et al, 1987;Ehrlich et al, 1988;Nakazawa et al, 1993), voltage-dependent Na' current (Ichikawa et al, 1991), and Ca2"-activated K+ channels (Kihira et al, 1990). Trifluoperazine inhibits Ca2" currents (Greenberg et al, 1987;Nakazawa et al, 1993), voltagedependent Na' current (Ichikawa et al, 1991), Ca2+-activated (McCann & Welsh, 1987;Kihira et al, 1990;Ikemoto et al, 1992) and ATP-sensitive (Muller et al, 1991) K+ channels, and GABA-activated Cl-current (Yang & Zorumski, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In ventricular and vascular myocytes, trifluoperazine depressed 'Ca, INa, and IK (Kldckner & Isenberg, 1987). Many of these studies (Greenberg et al, 1987;Klockner & Isenberg, 1987;McCann & Welsh, 1987;Ehrlich et al, 1988;Kihira et al, 1990;Nakazawa et al, 1993) included evidence suggesting that inhibition of channel activity was not mediated by calmodulin.…”
Section: Discussionmentioning
confidence: 99%